PROJECT-BASED LEARNING AS A PEDAGOGICAL LEVER IN A MASTER'S PROGRAM IN FRENCH: AN ALGERIAN EXPERIENCE AT THE UNIVERSITY OF EL-OUED - Mounir MILOUDI (Analele Universităţii din Craiova. Psihologie, Pedagogie)
In this research, we highlight an illustration of project-based pedagogy practices within the French department of El-Oued University. Following an experiment with a provoked-dominant approach, based on participant observation and a combination of structured and semi-structured interviews conducted in the university environment of the second year Master’s program during the postpandemic period, the findings reveal that project-based pedagogy positively impacts knowledge development in this context. The synthesis leads to the conclusion that this pedagogy enables students to engage in group work and research to achieve a collective goal. Furthermore, it provides students with the opportunity to learn both within the university (academic knowledge) and beyond (social knowledge), opening up new perspectives for the country's higher education institutions.